Developing Computer-Based Test (CBT) to Improve Students’ Achievement - Ika Irawati; Ita Fitriati (IJECA (International Journal of Education and Curriculum Application), 2018)
This research aims to develop Computer-Based Test (CBT) by using hot potatoes software, which is believed to be able to improve students’ achievement. Formative and summative questions were previously given using paper only, making the questions presented less interactive, resulting in low achievement of the students. This new procedure was adapted from ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation). The development of the model results in the creation of a package called Computer based Test-English Computer (CBT-EC) that contains 9 sub-packages, divided into two divisions. The first division is composed of 8 packages that contain formative tests, where as the second division consists of 1 package of summative tests. Data of this research were collected using tests and questionnaires. The test instrument used multiple choices with formative form consists of 15 questions from each chapter, while summative form consists of 120 questions. Students’ responses were measured by distributing the questionnaires about the usage of CBT-EC product to 10 students. The questionnaires were given to the media expert and material expert to assess their feasibility. The results showed that the expert of material gave 79 out of 84 maximum point, or almost excellent, meaning that the questionnaires developed as the product of CBT-EC are worth implemented. Meanwhile, the assessment of the media expert gave a score of 63 out of 68 maximum points classified as good, meaning that the CBT-EC product is feasible to be implemented. Based on learning result from the formative and summative test, there was an increase of the students' achievement. In formative test, the students got the average score of 69%, whereas in summative test they recorded average score of 79%. In conclusion, CBT-EC product could increase students’ achievement.